Evaluation of solar powered water pumping system: the case study of three selected Abattoirs in Ibadan, Nigeria - Temitope Raphael Ayodele; Ayodeji Samson Olatunji Ogunjuyigbe; Omolola Anuoluwa Adeniran (International Journal of Sustainable Engineering, 2019)
In this paper, detailed and comprehensive analysis of the technical, environmental and economic benefits of providing adequate water supply using solar PV system for three selected abattoirs (Bodija, Akinyele and Iyana church abattoirs) in Ibadan are presented. First, an estimate of average daily water requirement for slaughtering and cleaning cattle is obtained for each of the abattoir. This was achieved through oral interviews conducted at the different abattoirs to arrive at a reliable estimate. Thereafter, the total water requirement, the water storage capacity and the electrical load requirement necessary for the sizing of solar PV system that will enhance the smooth operation of the abattoir are determined. Some of the key results revealed that the water requirements of the abattoirs are 208,780, 91,632 and 78,590 l/week, respectively. The most suitable submersible pump for the three abattoirs is 60GS50 (5hp, 60gallon/min Goulds series). The cost of pumping water and providing lighting for smooth operation of the abattoirs are $0.23, $0.21 and $0.19, respectively. The results also show that 16,300, 15,200 and 14,600 kg/yr of carbon dioxide as well as 46.37, 43.36 and 41.45 kg/yr of carbon monoxide could be avoided, respectively with the implementation of the project.